CERAMICS FROM THE BURIALS OF SEPARATE MOUND GROUP NO 7 OF THE PALASA-SYRT BURIAL MOUND OF THE 4th-5th cc - Magomedov, U A; Gmyra, L B (History, Archeology and Ethnography of the Caucasus, 2016)
The article presents the results of the latest studies of the Palasa-Syrt burial mound (Southern Dagestan) of the 4th-5th centuries, conducted in 2016. The authors of the article focus on the analysis of the collection of ceramic vessels from separate mound group No. 7, consider the peculiarities of this collection (various types of vessels, their characteristics and period of their household use), as well as its similarity to the collections of ceramics from other burial groups of the mound
Keywords: Palasa-Syrt burial mound; mound group No.7; ceramic vessels; typological analysis of ceramics